Rancang Bangun Sistem Informasi Geografis Pemetaan lokasi dan spesifikasi Hotel di Kota Palopo Berbasis Website - Hardiana, Hardiana; Akramunisa, Akramunisa (Patria Artha Technological Journal, 2021)
Palopo as one of the cities in South Sulawesi Province that is developing, especially in the field of tourism as conveyed by Andi Enceng as the Tourism Cadre of Palopo City, then Palopo was also appointed as the host of national activities such as national seminars of universities and international conference ICONSS. This makes many tourists who visit not only want to enjoy the beauty of nature, culture and so on but also to attend national activities carried out in palopo city, so that facilities and infrastructure related to lodging is needed in palopo city such as one of them is a hotel. However, information about the location of the inn is still not widely known. The information they get is less accurate in terms of geography, of course the limitations of information will be an obstacle for people who want to travel, especially for those who live outside palopo city to find information on the location of a nearby hotel location. The purpose of this research is to create a design of geographic information system mapping location and specifications of hotels in palopo city basedwebsite design interface and database system, make the system in accordance with the design that has been created and implement the system that has been created and conduct tests on the system. In data collection, the authors used methods of literature studies, observations and interviews. Meanwhile, in the development of the author's system using research and development method refers to the waterfall model. The software used is sublime text as text editor, PHP as programming language, MySQL for database management and xampp as its server. Testing techniques used in this system is black box testing techniques, Based on the tests that have been done that the design of geographic information system mapping location and specifications of hotels in the city of Palopo based website is feasible and in accordance with the required functions. The expected results in this study design this website provides all the data related to hotels in palopo city and has been adjusted in advance so as to facilitate parties in operating the system.